Just beautiful green herbs: use of plants in cultural practices in Bukovina and Roztochya, Western Ukraine - N. Stryamets; M. F. Fontefrancesco; G. Mattalia; J. Prakofjewa; A. Pieroni; R. Kalle; G. Stryamets; R. Sõukand (BMC, 2021)
Abstract Background The use of plants in rituals is a little explored corner of biocultural diversity which has developed through time within a complex socio-ecological system. Indeed, rituals are complex interactions between humans and biodiversity shaped by history, culture, and ethnic belonging. Yet, in Western Ukraine, such rituals were forbidden for over 50 years (1939-1991). The current revival of rituals by rural inhabitants is an untapped reservoir of local ecological knowledge. The aim of the present study was to identify the ritual use of wild and cultivated plants in two regions of Western Ukraine, Bukovina and Roztochya, and to compare the findings with historical data. Moreover, we analyzed attitudes toward the ritual use of plants and interactions with the local environment. Methods We conducted 31 in-depth semi-structured interviews among Orthodox Hutsuls of Bukovina and 16 interviews among Greek Catholic rural inhabitants of Roztochya during summer 2018 focusing on the ritual uses of plants. Results We documented  28 plant taxa among Bukovinian Hutsuls and 58 plant taxa among inhabitants in Roztochya that were used in 7 religious festivals (of which two were celebrated differently in the two communities). Plants were mainly used in bouquets, but also for decorating churches and houses or in fruit baskets. In both communities, almost 25% of the interviewees could not name the plants they collected for bouquets, but rather referred to "just beautiful green herbs" one can get in meadows, forests, and gardens. Comparison with historical data shows a smaller number of taxa currently used (wild taxa have been lost), yet the persistence of 18 taxa used both now and a century ago. Conclusions Contemporary practices concerning the use of plants in Christian rituals in Bukovina and Roztochya can be contextualized in the broader phenomenon of the revitalization of traditional environmental knowledge and practices that have characterized Europe over the past 30 years and in particular Eastern Europe after socialism. The current religious use of plants is to a certain extent the revitalization of historical rituals supported by various internal (knowledge from older generations) and external (church authorities and fashion in the region) drivers. Further research should address changes in regions with longer and more severe prohibition of religious practices and their revival.